Raising the Profile of Clinical Engineering Through Effective Technology Management - Greenwood, Kim; Janvier, Marie-Ange; Zhang, Y. Rachel; Heggie, Gaetanne; Yazdanpanah, Marjan (CMBES Proceedings, 2013)
No Abstract